PELAKSANAAN ANALISIS MENGENAI DAMPAK LINGKUNGAN SOSIAL PABRIK KARET PT. BANGKINANG TERHADAP MASYARAKAT - Amanila, Rissa; Sujianto, Sujianto; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Implementation of Social Environmental Impact Analysis of Rubber Factory PT. Bangkinang Against Society. This study aims to find out and analyze the social environmental impacts of rubber factories for the communities surrounding the factory. The research informants consisted of industry groups, communities, and related institutions. Technique of collecting data by observation, interview, and literature study. Data analysis used qualitative descriptive method. In addition, SWOT analysis is used to see and study the factors that become the strengths and weaknesses as well as the factors that are the opportunities and threats for the rubber factory PT. Bangkinang and the surrounding community. The result of this research can be concluded that Rubber Factory PT. Bangkinang Kelurahan Tangkerang Tengah Kota Pekanbaru based on SWOT analysis, position or location of rubber factory PT. Bangkinang is now in a densely populated area likely to have more negative impacts than positive.